Synthesis of gold/polydopamine composite surfaces on glass substrates for localized surface plasmon resonance and catalysis. (20th April 2017) - Yu, Jianying; Lu, Shixiang; Xu, Wenguo; He, Ge; He, Dongsheng
Abstract : Composite materials of polydopamine (PDA) and gold nanoparticles on glass substrates (Au/PDA@slide) were obtained via a simple chemical process. First, PDA films (PDA@slide) were formed by immersing slides in 20 mg ml −1 dopamine aqueous solution at pH = 8.5 for 1 h. Then, PDA@slide was dipped in 0.02 M chloroauric acid (HAuCl4 ) aqueous solution for a certain time, Au/PDA@slide being formed. Gold nanoparticles were obtained by the reductive properties of PDA. The morphology and chemical composition of the composite material were characterized using scanning electron microscopy, X‐ray diffraction and X‐ray photoelectron spectroscopy. The catalytic properties of Au/PDA@slide were evaluated using the reduction of 4‐nitrophenol (4‐NP) in the presence of sodium borohydride (NaBH4 ) aqueous solution at room temperature. The catalytic activity of the optimal Au/PDA@slide was so satisfactory that the reduction of 4‐NP was completed within 10 min. Moreover, the Au/PDA@slide composite material was stable up to five cycles without significant loss of its catalytic activity. In addition, Au/PDA@slide also exhibited photocatalytic ability, photodegrading 2.5 ml of 17.5 mg l −1 methyl orange in 100 min. By measuring the UV–visible absorption bands of Au/PDA@slide, it was proved that the condition of the strongest surface plasmon resonance of Au/PDA@slide was the optimal condition for catalytic reduction of 4‐NP. Abstract : Au/polydopamine (PDA) composite surfaces on glass substrates were prepared with PDA as both reducing and adhesion agent. This Au/PDA@slide exhibited high efficiency for the reduction of 4‐nitrophenol and photodegradation of methyl orange.